Genetic Variation in the Syntaxin-Binding Protein STXBP5 in Type 1 von Willebrand Disease Patients - Lind-Halldén, Christina; Manderstedt, Eric; Carlberg, Daniel; Lethagen, Stefan; Halldén, Christer (Thrombosis and Haemostasis, 2018)
von Willebrand factor (VWF) levels in healthy individuals and in patients with type 1 von Willebrand disease (VWD) are influenced by genetic variation in several genes, for example, VWF , ABO and STXBP5 . Here, we comprehensively screen for STXBP5 variants and investigate their association with type 1 VWD in Swedish patients and controls. The coding region of the STXBP5 gene was re-sequenced in 107 type 1 VWD patients and the detected variants were genotyped in the type 1 VWD population and a Swedish control population (464 individuals). The functional effects of missense alleles were predicted in silico and the pattern of genetic variation in STXBP5 was analysed. Re-sequencing of 107 type 1 VWD patients identified three missense and three synonymous variants in the coding sequence of STXBP5 . The low-frequency missense variants rs144099092 (0.005) and rs148830578 (0.029) were predicted to be damaging, but were not accumulated in patients. No other rare candidate mutations were detected. STXBP5 showed a high level of linkage disequilibrium and a low overall nucleotide diversity of π = 3.2 × 10 −4 indicating intolerance to variants affecting protein function. Three previously type 1 VWD-associated single nucleotide polymorphisms were located on one haplotype that showed an increased frequency in patients versus controls. No differences in messenger ribonucleic acid abundance among haplotypes could be found using Genotype-Tissue Expression project data. In conclusion, a haplotype containing the STXBP5 Asn436Ser (rs1039084) mutation is associated with type 1 VWD and no rare STXBP5 mutations contribute to type 1 VWD in the Swedish population.
Keywords: mutation; re-sequence; STXBP5; von Willebrand disease; VWD